2018
DOI: 10.3390/met8121022
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Thermally Aged DSS 2304 against Localized Corrosion Attack

Abstract: In this paper, the effects of thermal aging in the 650–850 °C range on the localized corrosion behaviour of duplex stainless steel (DSS) 2304 was investigated. Pitting corrosion resistance was assessed by pitting potential (Epitt) and critical pitting temperature (CPT) determination, while the degree of sensitisation (DOS) to intergranular corrosion (IGC) was evaluated by double loop electrochemical potentiokinetic reactivation (DL-EPR). The susceptibility to stress corrosion cracking (SCC), evaluated in stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…Aging at 650 and 750 °C created a reduction of pitting corrosion resistance, in comparison to the as-received sample (CPT value of 49.7 °C), particularly after the longest aging time (60 min). On the contrary, in agreement with previous results on LDSS 2101 and DSS 2304 [7,10], at 850 °C a recovery of pitting resistance in comparison to the corresponding aging at 750 °C was obtained. In Figure 5, the micrographs of the as-received LDSS 2404 electrode after CPT test, before and after etching with Beraha's reagent, evidenced that pits developed in the α phase and selectively grew within this phase.…”
Section: Wt% Sisupporting
confidence: 92%
See 3 more Smart Citations
“…Aging at 650 and 750 °C created a reduction of pitting corrosion resistance, in comparison to the as-received sample (CPT value of 49.7 °C), particularly after the longest aging time (60 min). On the contrary, in agreement with previous results on LDSS 2101 and DSS 2304 [7,10], at 850 °C a recovery of pitting resistance in comparison to the corresponding aging at 750 °C was obtained. In Figure 5, the micrographs of the as-received LDSS 2404 electrode after CPT test, before and after etching with Beraha's reagent, evidenced that pits developed in the α phase and selectively grew within this phase.…”
Section: Wt% Sisupporting
confidence: 92%
“…Mechanical and corrosion properties in duplex stainless steels (DSSs) closely depend on microstructural characteristics including α/γ phase ratio and secondary phase formation during production or welding operations. In particular, in previous works [6][7][8][9][10][11], we found that short-term thermal aging between 650 and 850 • C negatively affected both localized and stress corrosion cracking (SCC) resistance of LDSS 2101 and DSS 2304. In 2101 grade, because of its high N alloyed-content (0.22 wt.%), thermal aging from 5 to 30 min in the 650-850 • C range mainly induced chromium nitride formation at grain boundaries.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…The study by Zanotto et al found that microstructural modifications imparted by heat treatment produced sensitization and influenced the localized corrosion and stress corrosion cracking of 2304 duplex stainless steel [5]. Pitting and intergranular corrosion mainly initiated in Cr-and Mo-depleted regions (ferrite/austenite interphases), near to the Cr 23 C 6 precipitates within the γ 2 and γ phases, then propagated in the ferrite matrix.…”
mentioning
confidence: 99%